2016
DOI: 10.1016/j.immuni.2016.03.012
|View full text |Cite
|
Sign up to set email alerts
|

Expansion and Activation of CD103+ Dendritic Cell Progenitors at the Tumor Site Enhances Tumor Responses to Therapeutic PD-L1 and BRAF Inhibition

Abstract: Large numbers of melanoma lesions develop resistance to targeted inhibition of mutant BRAF or fail to respond to checkpoint blockade. We explored whether modulation of intratumoral antigen presenting cells (APCs) could increase responses to these therapies. Using mouse melanoma models, we found that CD103+ dendritic cells (DCs) were the only APCs transporting intact antigens to the lymph nodes and priming tumor-specific CD8+ T cells. CD103+ DCs were required to promote anti-tumoral effects upon blockade of the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

56
1,050
0
2

Year Published

2016
2016
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 964 publications
(1,108 citation statements)
references
References 46 publications
56
1,050
0
2
Order By: Relevance
“…In the B-Raf/PTEN −/− / β-catenin genetically engineered mouse model, this has been pursued by generating bone marrow-derived DCs using Flt3L followed by activation with the TLR3 agonist poly I:C. Injection of these DCs directly into the tumor microenvironment restored T cell priming, effector T cell recruitment, and caused partial tumor shrinkage, which was amplified with co-administration of anti-CT-LA-4 and anti-PD-L1 mAbs [102]. In a related strategy, systemic administration of Flt3L to increase Batf3 DCs in the tumor microenvironment, combined with intratumoral injection of poly I:C had a similar effect [46]. These are approaches that are immediately testable in the clinic with available reagents.…”
Section: Therapeutic Opportunitiesmentioning
confidence: 96%
See 2 more Smart Citations
“…In the B-Raf/PTEN −/− / β-catenin genetically engineered mouse model, this has been pursued by generating bone marrow-derived DCs using Flt3L followed by activation with the TLR3 agonist poly I:C. Injection of these DCs directly into the tumor microenvironment restored T cell priming, effector T cell recruitment, and caused partial tumor shrinkage, which was amplified with co-administration of anti-CT-LA-4 and anti-PD-L1 mAbs [102]. In a related strategy, systemic administration of Flt3L to increase Batf3 DCs in the tumor microenvironment, combined with intratumoral injection of poly I:C had a similar effect [46]. These are approaches that are immediately testable in the clinic with available reagents.…”
Section: Therapeutic Opportunitiesmentioning
confidence: 96%
“…Type I IFNs are also expressed by leukocytes in the tumor and tumor-draining lymph node in an autochthonous melanoma model driven by melanocyte-specific activating mutation in BRAF and deletion of PTEN [45]. Recently, it was demonstrated that CD103 + DCs are uniquely capable of transporting tumor-derived antigens to the tumor-draining lymph node in a CCR7-dependent manner, where they prime antigen-specific CD8 + T cells [46]. This process was augmented in an IFNAR-dependent manner, revealed by a combination treatment of tumor-bearing mice with Fms-related tyrosine kinase 3 ligand (Flt3L) and intratumoral injection of polyinosinic:polycytidylic acid (poly I:C).…”
Section: The Central Role For Type I Ifns and Batf3 Dcsmentioning
confidence: 99%
See 1 more Smart Citation
“…caused by chronic inflammation of synovial tissue. During the onset of RA, an acute inflammation of the synovial lining (synovitis) leads to an extensive expansion of the corresponding cells (i.e., pannus formation and inflammatory cytokines), massive infiltration of leukocytes of the innate immune system (i.e., T and B cells, plasmocytes, and macrophages), and synovial fibroblast proliferation (8)(9)(10). The latter are regarded as effector cells responsible for cartilage and bone destruction in RA.…”
Section: Discussionmentioning
confidence: 99%
“…This may or may not be linked to the role of activated mononuclear phagocytes/macrophages in the outcome of checkpoint therapy [45] where it has been shown that the induction of the CD103 + marker on DCs is an absolute required for PD-1-based therapy to be effective in a murine model. This is of interest as a review of many different vaccine studies over the last two decades highlighted the excellent long-term outcome of patients given a heat-killed mycobacterium vaccine preparation (also known as SRL-172) with stage IV melanoma patients achieving similar 5-and 8-year survivals to that reported using ipilimumab.…”
Section: Novel Immunotherapeutics and Future Perspectivementioning
confidence: 99%